HUBUNGAN ANTARA DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR SATUAN POLISI PAMONG PRAJA KABUPATEN KUTAI TIMUR - Ardi, Kila (PREDIKSI, 2016)
This research aims to find out whether the development of working discipline have a positive impact on the performance of the employees of Kantor Satuan Polisi Pamong Praja Kabupaten Kutai Timur. The results of the study showed there is a positive signal and significant influence between variables working discipline with a variable performance of employees at Kantor Satuan Polisi Pamong Praja Kabupaten Kutai Timur. It could be known from the results of the test statistic koefisiensi correlation (r) was 0,287 which means there is a positive influence between both variables. Data analysis results obtained a determination coefficient (r2), USD 0,082. This means that the variables that occur in the variable performance of civil servants 8.2 % can be explained through variants which occurs on variabeel working discipline or in other words that the performance of the employees of 8.2 % influenced by working discipline, the remaining 91,8 % influenced by other factors or other variables which are not included in this research.